Static Hedging of Exotic Options - Carr, Peter; Ellis, Katrina; Gupta, Vishal (Journal of Finance, 1998)
This paper develops static hedges for several exotic options using standard options. The method relies on a relationship between European puts and calls with different strike prices. The analysis allows for constant volatility or for volatility smiles or frowns.